Patient‐reported outcomes in women with breast cancer enrolled in a dual‐center, double‐blind, randomized controlled trial assessing the effect of acupuncture in reducing aromatase inhibitor‐induced musculoskeletal symptoms. Issue 3 (23rd December 2013) - Bao, Ting; Cai, Ling; Snyder, Claire; Betts, Kelly; Tarpinian, Karineh; Gould, Jeff; Jeter, Stacie; Medeiros, Michelle; Chumsri, Saranya; Bardia, Aditya; Tan, Ming; Singh, Harvinder; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Aromatase inhibitors (AIs) have been associated with decrements in patient‐reported outcomes (PROs). The objective of this study was to assess whether real acupuncture (RA), compared with sham acupuncture (SA), improves PROs in patients with breast cancer who are receiving an adjuvant AI. METHODS Postmenopausal women with a stage 0 through III breast cancer who received an AI and had treatment‐associated musculoskeletal symptoms were randomized to receive 8 weekly RA versus SA in a dual‐center, randomized controlled trial. The National Surgical Adjuvant Breast and Bowel Project (NSABP) menopausal symptoms questionnaire, the Center for Epidemiological Studies Depression (CESD) scale, the Hospital Anxiety and Depression Scale (HADS), the Pittsburgh Sleep Quality Index (PSQI), the hot flash daily diary, the Hot Flash‐Related Daily Interference Scale (HFRDI), and the European quality‐of‐life survey (EuroQol) were used to assess PROs at baseline and at 4weeks, 8 weeks, and 12 weeks. RESULTS The intention‐to‐treat analysis included 23 patients in the RA arm and 24 patients in the SA arm. There were no significant differences in baseline characteristics between the 2 groups. Compared with baseline, scores in the RA arm improved significantly at week 8 on the CESD (P = .022), hot flash severity (P = .006), hot flash frequency (P = .011), the HFRDI (P = .014), and NSABP menopausal symptoms (P = .022); scores in the SA arm improved significantly on the EuroQol (P = .022), the HFRDI (P = .043), and NSABP menopausal symptoms (P = .005). Post‐hoc analysis indicated that African American patients (n = 9) benefited more from RA than SA compared with non‐African American patients (n = 38) in reducing hot flash severity (P < .001) and frequency (P < .001) scores. CONCLUSIONS Both RA and SA were associated with improvement in PROs among patients with breast cancer who were receiving AIs, and no significant difference was detected between arms. Racial differences in response to acupuncture warrant further study. Cancer 2014;120:381–389. © 2013 American Cancer Society.